Transurethral ventral buccal mucosal inlay grafting: a narrative review - Cedars, Benjamin; Nikolavsky, Dmitriy (Translational andrology and urology, 2025)
Urethral strictures involving the meatus and fossa navicularis (FN) account for up to 18% of cases, presenting unique diagnostic and therapeutic challenges. This review explores the history and current management strategies, including minimally invasive endoscopic techniques and reconstructive options such as flap and buccal mucosal graft (BMG) urethroplasty. Open urethroplasty remains the gold standard, particularly for complex cases, but it carries undesirable risks such as dehiscence and fistula formation. We will review transurethral approaches to avoid these risks and provide a step-by-step explanation for the ventral inlay BMG FN urethroplasty. A focused review of the literature was performed using the PubMed database with the following search terms: "transurethral", "transmeatal", "urethroplasty", and "fossa navicularis". English language articles were included, and detailed review was carried out to select the relevant articles. Recent advancements include transurethral approaches that minimize external incisions and associated complications, demonstrating high success rates while preserving functional and aesthetic outcomes. Key elements of the procedure include ventral scar tissue resection, harvest of a tear-shaped BMG, and use of double-armed sutures to allow for external knot tying. This review highlights the importance of refining and innovating techniques to optimize patient outcomes in managing FN strictures, most recently via transurethral augmentation with BMG.